Comparison of Agreement Law in Indonesia and Malaysia: Phenomenon of Standard Agreement Practices - Manurung, Shenti Agustini; Irawati, Jovita; Sudirman, Lu; Agustianto, Agustianto; Farahdina, Farahdina (SASI, 2025)
Introduction: Indonesia and Malaysia are countries with fairly good economic levels in the ASEAN. Economic growth in the business world also has an influence on contract law because the phenomenon that occurs is the use of standard agreement models in the business world to make business processes more effective and efficient.Purposes of the Research: The aim of this research is to analyze the differences in contract law in Indonesia and Malaysia, also describe the phenomenon of standard agreement practices that occur in Indonesia and Malaysia, and analyze the validity of standard agreements that apply in Indonesia and Malaysia.Methods of the Research: The research method used is normative juridical. The type of study used is through literature study. The type of data used is secondary data consisting of primary legal materials, namely the Civil Code, the Malaysian Contracts Act 1950, the 1957 Sale of Goods Deed.Results Main Findings of the Research: The research results show that Indonesia and Malaysia are countries that have implemented standard agreement. These two countries also have a legal basis that allows standard agreements to come into force on the condition that there must be clauses that emphasize the rights and obligations of the parties to achieve justice.